Research on Properties of High-Performance Cement Mortar for Semiflexible Pavement - Yazhen Sun; Yuanyuan Cheng; Min Ding; Xuezhong Yuan; Jinchang Wang (Advances in Materials Science and Engineering)
Cement mortar is one of the most important components of semiflexible pavement materials; however, the effects of cement mortar formulation on the performance and the grouting rate are rarely studied. Therefore, the optimum formulation of high-performance cement mortar (HPCM) for different types and contents was studied, and the grouting effect of the cement mortar was studied by rutting tests. The results show that polycarboxylate superplasticizer, expansion admixture, and accelerating admixture have different influences on the workability, the strength, and the drying shrinkage of HPCM, and the working ability of HPCM is good by adding these three admixtures. The strength at 7 days is 1.3 to 4 times that of the existing specifications, and the shrinkage rate is less than 0.2. The HPCM has higher early strength, and the strength development is stable in the later period compared with the other research studies. The semiflexible material has better pavement performance when the grouting rate is greater than 90%.